AL-IDHAFAH, AL-NA’AT, AND AL-TAUKID: STRUCTURAL RELATIONS BETWEEN ELEMENTS IN ARABIC SYNTAX - Sulfadli; Muslimin Resi; Hamzah (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This research aims to explain the structural relations between al-idhāfah, al-naʿt, and al-tawkīd in Arabic syntax and to delineate how their interaction influences meaning formation and functional distribution within the nominal phrase. This study is conducted because previous research has tended to discuss these three elements separately, resulting in a lack of an integrated analytical model that describes the hierarchical and semantic relationships between them. The study employs a qualitative-descriptive approach, analyzing data drawn from classical nahwu texts, modern Arabic corpora, and relevant contemporary research. Data were classified based on the patterns of element occurrence and analyzed through structural syntactic analysis methods to identify their functions, positions, and i‘rāb (inflectional) implications. The results indicate that idhāfah serves as a marker of possessive relations and semantic restriction, naʿt functions to provide descriptive modification that clarifies the referent, and tawkīd reinforces the reference both structurally and semantically. These three form dependency patterns that influence each other when present within a single phrasal construction. The novelty of this research lies in the formulation of an integrative relational model that combines syntactic functions, hierarchical structures, and semantic implications into a single operational analytical framework. This model provides a more comprehensive understanding compared to previous fragmentary studies. These findings have important implications for the teaching of nahwu, the analysis of modern Arabic discourse, and the development of computational linguistic applications that require more accurate mapping of nominal structures.